Can the state replace private capital investors? Public financing of venture capital in Hungary - Judit Karsai (Hungarian Academy of Sciences, Institute of Economics, 2004)
It is generally accepted that venture capital exerts a positive influence on economic development, and Hungarian economic policy, too, regards it as a means to accelerate economic growth, enhance the export capacity of companies, improve employment, increase tax revenues, investments and research and development expenditures, that is, to boost the overall competitiveness of the country. Although Hungary boasts an advanced venture capital industry in regional comparison, the capital supply of small/startup companies especially is still unresolved. The successive Hungarian governments having come to power since the change of the economic and political regime declared almost without exception the importance of venture capital, and made efforts to contribute to raising its supply. These efforts, however, have been rather ineffective due to their almost exclusive reliance on direct state intervention and disregard for the much more successful western solutions stimulating private sector venture capital investors. The present paper first describes the reasons, areas, direct and indirect forms of state intervention in the venture capital industry. Subsequently, it surveys its specific reasons and practice so far on the Hungarian venture capital market. It highlights the essential difference in approach reflected by the Hungarian and the western experiences, respectively, and makes a proposal as to how the state could promote the development of the venture capital market more effectively and in a more market-oriented way, with special regard to Hungarys prospective accession to the European Union in 2004. Accordingly, the state should avoid direct capital investment in companies, bypassing the private sector; it should supplement the funds of private investors as co-financier, and control co-operation with them by reducing the risks and increasing the profits associated with investments enjoying state preference for private investors. This would allow the state to realise its economy and venture capital industry development objectives simultaneously.
Keywords: 330; venture capital; public policy